Building a mobile application for HIV Post-Exposure Prophylaxis. - Silva, Alexis Pereira da; Barbosa, Barbara Jacqueline Peres; Camargo, Robinson Fernandes; Nichiata, Lucia Yasuko Izumi (Acta Paulista de Enfermagem, 2021)
Objective: To describe the process of building a mobile application to support HIV Post-Exposure Prophylaxis and analyze how healthcare professionals respond to the attributes of its usability. Methods: A technological production study, built in four phases, between 2016 and 2018: composition of the app's central content; gathering a set of tools for the prototype; prototype testing; testing usability attributes using the empirical method. The PEPtec application was built based on national and international guidelines for post-exposure prophylaxis for HIV. Healthcare professionals' responses about usability attributes (ease, utility, interface and use of the app) were analyzed using a semi-structured questionnaire applied to 28 professionals from the services for people with Sexually Transmitted Infections of a Health Coordination of the municipality of São Paulo (SP), Brazil. Results: The application was made available for Android and iOS. It was personalized for healthcare professionals' cell phones to support decision-making in the indication of HIV Post-Exposure Prophylaxis. Regarding the application interface, the professionals considered that the colors and icons were pleasant and easy to identify. In the usability analysis, professionals reported ease of use, gained skills and were able to navigate through all screens. Conclusion: The mobile application responds to the interests of these professionals in the outcome of indication for Post-Exposure HIV Prophylaxis through this technological tool.